Integrative and complementary healthcare practices for hypertension: a summary of recommended clinical guidelines - Marcus Tolentino Silva; Daniel Miele Amado; Paulo Roberto Sousa Rocha; Jorge Otávio Maia Barreto (Epidemiologia e Serviços de Saúde, 2025)
Abstract Objective Identifying the main uses of integrative and complementary healthcare practices (ICPHPs) in managing systemic arterial hypertension in adults. Methods Evidence summary. With eligibility criteria for the clinical guidelines from the Grading of Recommendations, Assessment, Development and Evaluation system and others that addressed ICPHPs hypertension, with no language or date restrictions. Medline, Embase and Scopus were the databases consulted. The Appraisal of Guidelines for Research and Evaluation II tool was used for risk of bias assessment, focusing on methodological rigor. The results were then summarized narratively, grouping the recommendations by outcome and analyzing commonalities and differences between the included guidelines. Results Eight clinical guidelines were included in this evidence summary, selected from 560 records initially identified. The most common interventions were meditation, yoga, breathing techniques, tai chi and mindfulness, with a positive impact on blood pressure, stress control and patients’ quality of life. Most guidelines recommended these practices for hypertension control, based on moderate quality evidence with a strong recommendation. Conclusion The results of this summary indicate that HCPs are effective and safe strategies in the complementary management for hypertension, suggesting a more holistic and less medicalized approach to managing the condition.